A Living Systems Theory of Vocational Behavior and Development - Vondracek, Fred; Ford, Donald; Porfeli, Erik (Brill | Sense, 2014)
The Living Systems Theory of Vocational Behavior and Development (LSVD) explains and illustrates the processes by which individuals construct their work experiences, vocational pathways and career patterns through episodes of interaction with affordances they recognize within their contexts, and how counseling can facilitate those processes. The LSVD was created by combining the scientifically based systems theory that explicates the dynamics of all aspects of human functioning and development, called Humans as Self-Constructing Living Systems, with important ideas about vocational behavior and development. The resulting integrative theory represents the individual person as a dynamic, self-directing and self-constructing entity, i.e., a living system. Behavior Episodes (BEs) are the fundamental, person-in-context, dynamic units of analysis that serve as the "building blocks" by which individuals construct and retain their experiences in patterns that can be reactivated to facilitate future BEs. The book describes how individuals' history of satisfying BEs and their current activities provide the means by which vocational and career counselors can assist them to create satisfying vocational pathways. It also describes for researchers how new, non-linear, person-centered, quantitative and qualitative research methods can be used to analyze BE patterns to advance understanding of person-level processes that play key roles in individuals' vocational behavior and development. The LSVD was designed to be not just an integrative framework for the field of career development, but also to reconnect the field to related areas such as human resources and industrial-organizational psychology and to the range of human sciences that have already embraced a living systems theoretical model